2021
DOI: 10.3390/antiox10050707
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Foliar Putrescine Application, Ammonium Exposure, and Heat Stress on Antioxidant Compounds in Cauliflower Waste

Abstract: This work has been focused on the study of how we can affect the short heat stress on the bioactive compounds content. Some recent investigations have observed that management of nitrogen fertilization can alleviate short-term heat effects on plants. Additionally, the short-term heat stress can be also ameliorated by using putrescine, a polyamine, due to its crucial role in the adaptation of plants to heat stress Therefore, different NO3−/NH4+ ratios and a foliar putrescine treatment have been used in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…After the extraction of bioactive compounds, the residual biomass represents a feedstock for energy production, for example by anaerobic digestion [ 22 ]. With respect to globe artichoke, cauliflower byproducts valorization received substantially minor attention with only a few examples relative to the extraction of phenolic antioxidants [ 23 , 24 , 25 ], dietary fibers [ 26 ], and peptide hydrolysates [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the extraction of bioactive compounds, the residual biomass represents a feedstock for energy production, for example by anaerobic digestion [ 22 ]. With respect to globe artichoke, cauliflower byproducts valorization received substantially minor attention with only a few examples relative to the extraction of phenolic antioxidants [ 23 , 24 , 25 ], dietary fibers [ 26 ], and peptide hydrolysates [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under the present conditions, in the leaves, only SPM treatment could influence the SA content, as under L1 and L3 it decreased, but under L2 it increased. Although the expression level of PAL dramatically increased in SPM-treated plants under L3, this could be related only to the effect of higher PAs on the synthesis of phenolic compounds, which are more dominant under low light condition [39,67]. Changes in the expression pattern of CS or ICS were not closely related to the SA content, except for the SPM-treated plants under L3, where the lowest SA and ICS expression was measured.…”
Section: Effect Of Light Quantity On Salicylic Acid and Abscisic Acid Synthesis And Its Relation To Pa Metabolismmentioning
confidence: 80%
“…Numerous valuable studies have been published on the investigation of PA content and metabolism either under normal growth conditions or during biotic or abiotic stresses in various plant species [28][29][30][31][32][33][34][35][36][37][38]. On the other hand, several studies have been published on monitoring the protective effect of exogenous PAs [8][9][10][11]13,14,[39][40][41]. Exogenous PAs provided protection under osmotic and cadmium stress [8,9], but the mode of action and the degree of protection depended on the alteration in the PA metabolism; thus, it has been demonstrated that "the more PA, the better" statement cannot be generalized [10,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Gómez et al ( 2010) pointed out in tomato that MeJA produced a rapid increase in leaf export of photosynthates, which did not occur in pepper. Recent works have indicated that endogenous polyamines could participate in sustaining membrane integrity in cauliflower, as protectors against damage under stress conditions, through the stabilization of cell membranes (Collado-Gonzaĺez et al, 2021a;Collado-Gonzaĺez et al, 2021b), and therefore, they could have an effect in delaying leaf-related-senescence disorders. As previously indicated for other species, the collateral effect of MeJA associated with early senescence, can be effectively counteracted by the increase in the concentration of endogenous polyamines in specific pepper cultivars.…”
Section: Discussionmentioning
confidence: 99%